Projecting paranoia conspiratorial visions in American film - Pratt, Ray (Lawrence University Press of Kansas, 2001)
For decades American cinema has mirrored and promoted the postmodern anxieties and paranoid perceptions embedded in our society. Tapping into the moviegoing audience's own projected fears, many Hollywood films seem to confirm our belief that there are indeed secret sinister forces at work and that our lives are at risk because of them. Pratt revisits blockbusters and cult favorites alike and shows how their images of conspiracy have been fostered by the public's increasing distrust of large organizations, producing in turn a cinematic "narrative of resistance" that challenges the status quo. He offers Seven Days in May and Dr. Strangelove as signposts of Cold War hysteria; Chinatown, The Conversation, and Missing as clear reflections of our distrust of political and corporate elites in the wake of Vietnam and Watergate; and Blue Velvet and The Stepfather as dark countermyths to the "family values" touted by Ronald Reagan in the 1980s. He also considers gender paranoia in films like Klute, Fatal Attraction, and Silence of the Lambs and reminds us that sometimes, as in Serpico, our guardian police forces need a bit of guarding themselves.
Includes bibliographical references (p. 299-304) and index.
Keywords: Motion pictures -- Political aspects -- United States